Cytotoxic Activity of 2-O-β-glucopyranosil Cucurbitacin D from Benalu Batu (Begonia sp.) Growing in Morowali, Central Sulawesi - Muhammad Sulaiman Zubair; Walied Mohamed Alarif; Mohamed Ali Ghandourah; Syariful Anam; Ibrahim Jantan (Indonesian Journal of Chemistry, 2020)
Benalu batu (Begonia sp.) had been used traditionally as an anticancer medicinal plant by Wana tribe in Morowali, Central Sulawesi, This study aims to evaluate the cytotoxic activity of 2-O-β-glucopyranosil cucurbitacin D, isolated from the ethyl acetate soluble fraction of Benalu batu (Begonia sp.) and to determine its action on apoptosis induction. Benalu batu (Begonia sp.) herb was extracted by maceration using ethanol 96% as a solvent. Vacuum liquid column chromatography and preparative thin layer chromatography have been applied on fractionation and isolation of the compound. The structure elucidation was performed by extensive analysis of 1D/2D nuclear magnetic resonance (NMR) and Mass Spectrophotometer (MS). Cytotoxic activity against human breast adenocarcinoma (MCF-7) and human colon colorectal carcinoma (HCT-116) cell lines were performed by 5-diphenyltetrazolium bromide (MTT) method. Annexin V-FITC assay was employed to determine the apoptosis induction. 2-O-β-glucopyranosil cucurbitacin D showed potent cytotoxic activity against MCF-7 and HCT-116 with the IC50 of 19.913 and 0.002 μg/mL, respectively. Annexin V-FITC assay clearly exhibited the cytotoxic mechanism on MCF-7 and HCT-116 via apoptosis induction with a significant percentage of early and late apoptosis of 75.8 and 78.4%, respectively. This study reveals the potential cytotoxic activity of 2-O-β-glucopyranosil cucurbitacin D isolated from Benalu batu and its mechanism via apoptosis induction.